Legal Politics Of Corporate Responsibility In Indonesia’s Criminal Law - Wawan Septiawan; Abdul Patah Muzakir; Yudi Permana Saputra; Abdul Muflihun (Unram Law Review, 2019)
The purposes of this research are to know the decisionpublic policy by the government-related corporate responsibility in Indonesia’s Criminal Law, to know the corporate responsibility special laws in Indonesia, and also the mechanism to find out the corporate’s fault. The applied method in this research is normative-legal research. From the research result, it can be concluded that the Government of the Republic of Indonesia has to determine the latest version of Indonesia’s Criminal Law or revised several laws related to corporate criminal responsibility. In Indonesia’s Criminal Law, corporate criminal responsibility is not recognized, but the corporate responsibility is dispersed in special laws such as Law on Economy Crimes and Consumer Protection. To determined the corporate fault was taken from the manager or member of Board of Directors.